Управління ланцюгами постачання – аналіз і оцінка моделей і методів - Хачатурян, О. С.; Khachaturyan, О. (ЦНТУ, 2023)
В умовах ведення бізнесу, які постійно змінюються, виникає потреба в адаптації існуючих і створенні нових механізмів у логістиці. У роботі виконано огляд моделей, методів і концепцій, які використовуються при управлінні ланцюгами постачання в сучасних умовах. Пропонується умовно розділити моделі та методи логістики на загальнонаукові та спеціальні, котрі використовуються при об’єктному та процесному моделюванні. A study of models and methods of supply chain management was conducted. In an ever changing business conditions, the need has been identified for adapting existing and creating new mechanisms in logical stick. An overview is presented and an analytical assessment of models, methods and concepts used in supply chain management in modern conditions. Generalization of the experience of leading experts made it possible to conditionally divide the models and methods used in logistics into general scientific and special ones.
Supply chain management – evaluation of models and methods
Keywords: управління ланцюгами постачання; логістика; планування ланцюгів постачання; моделі і методи; цифрові технології; lancet supply management; logistics; lancet supply planning; models and methods; digital technologies